Marine Resources Management in Sorong Regency in Environmental Communication Perspective - Anna Agustina (Postgraduate, University of Mataram, 2023)
The potential of marine resources in Sorong district, West Papua is very abundant, especially in the fisheries sector and encourages the economy and development of the State and can prosper the surrounding community. Suboptimal utilization results in a less prosperous community so that many social conflicts occur that threaten the disintegration of the nation. This study aims to analyze the management of marine resources in Sorong Regency in the perspective of defense management using a descriptive qualitative research design. The results of this study show that the management of marine resources in Sorong Regency is still not effective and in accordance with the principles of sustainable development. The economic aspect, the lack of understanding of fishermen related to the marketing system results in oligarchs so that those who benefit a lot are not fishermen. Ecological aspects, the use of fishing gear that is not environmentally friendly such as fish bombs and cantrang results in damage to marine ecosystems. The social aspect, open access management has resulted in fisheries production, both capture and aquaculture, starting to decline.